Nontraditional Approaches with Nontraditional StudentsExperiences of Learning, Service and Identity Development - Suzanne M. Buglione (Adult Education Research Conference, 2015)
This phenomenological inquiry examines the lived experiences of highly nontraditional students enrolled in credit-bearing, undergraduate higher education courses, and engaged in pedagogy related to service and learning to examine civic and student identity development reflecting the extent to which students perceive these identities as marginalized
Keywords: nontraditional; service; identity; outgroup